Association between Obesity and Type 2 Diabetes Mellitus in Primary Health Care Settings in Eastern Indonesia: A Cross-Sectional Study - Kristina E. T. Lobho; Linros Susanti Noldi Tanu; Hendrika Ika; Violin Irene Ninef (Inspirasi Foundation, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) remains a major non-communicable disease and a growing public health concern globally and in Indonesia. Obesity is widely recognized as a key modifiable risk factor contributing to insulin resistance and the development of T2DM. In primary healthcare and community settings, evidence regarding the association between obesity and T2DM is essential to support effective preventive and promotive nursing interventions. Objective: This study aimed to analyze the association between obesity and Type 2 Diabetes Mellitus among patients in the working area of Sikumana Public Health Center, Kupang City. Method: This study employed a quantitative analytic observational design with a cross-sectional approach. The population consisted of 935 adult patients registered at Sikumana Public Health Center. A total of 93 respondents were selected using purposive sampling based on predefined inclusion and exclusion criteria. Obesity status was assessed using Body Mass Index (BMI), while T2DM status was obtained from secondary medical record data. Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test at a significance level of p ≤ 0.05. Results: The results showed that 51.6% of respondents were classified as obese. The proportion of obesity was higher among respondents with Type 2 Diabetes Mellitus compared to those without diabetes. Statistical analysis demonstrated a significant association between obesity and Type 2 Diabetes Mellitus (χ² = 12.081; p = 0.001). Conclusion: Obesity was significantly associated with Type 2 Diabetes Mellitus among patients in the working area of Sikumana Public Health Center. These findings highlight the importance of obesity prevention and weight management strategies as part of nursing-led health promotion and disease prevention programs to reduce the burden of Type 2 Diabetes Mellitus at the primary healthcare level.